Understanding choline bioavailability and utilization: first step toward personalizing choline nutrition - Goh, Ying Qi (2022)
Choline is an essential macronutrient involved in neurotransmitter synthesis, cell-membrane signaling, lipid transport, and methyl-group metabolism. Nevertheless, the vast majority are not meeting the recommended intake requirement. Choline deficiency is linked to nonalcoholic fatty liver disease, skeletal muscle atrophy, and neurodegenerative diseases. The conversion of dietary choline to trimethylamine by gut microbiota is known for its association with atherosclerosis and may contribute to choline deficiency. Choline-utilizing bacteria constitutes less than 1% of the gut community and is modulated by lifestyle interventions such as dietary patterns, antibiotics, and probiotics. In addition, choline utilization is also affected by genetic factors, further complicating the impact of choline on health. This review overviews the complex interplay between dietary intakes of choline, gut microbiota and genetic factors, and the subsequent impact on health. Understanding of gut microbiota metabolism of choline substrates and interindividual variability is warranted in the development of personalized choline nutrition.